Pengaruh CAR dan NPF terhadap Return on Aset dengan Pembiayaan Murabahah Sebagai Variabel Intervening di Bank Muamalat - Rida Amalia; Diharpi Herli Setyowati; Djoni Djatnika (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine the direct and indirect effect of Capital Adequacy Ratio and Non-Performing Financing on Return On Assets through Murabahah Financing as an intervening variable. The object of this research is Bank Muamalat Indonesia during the period 2009-2020. The data analysis technique used path analysis with the analysis tool SmartPLS software version 3.0. The data used is secondary data obtained from the quarterly published financial statements of Bank Muamalat for the period 2009-2020. The results of this study indicate the direct effect of CAR has a significant positive effect on Murabahah Financing, NPFt-1 has no effect on Murabahah Financing, CAR has no effect on ROA, NPFt-1 has a significant negative effect on ROA and Murabahah Financing has a significant negative effect on ROA, while the indirect effect it can be concluded that CAR has a significant negative effect on ROA and NPFt-1 has no effect on ROA through Murabahah Financing.